1970
DOI: 10.3329/ujzru.v25i0.323
|View full text |Cite
|
Sign up to set email alerts
|

Present status of pond fishery resources and livelihood of the fish farmers at Mohanpur Upazila in Rajshahi District

Abstract: A survey was conducted in Mohanpur Upazila, Rajshahi to determine the pond fishery resources and the livelihood status of fish farmers for a period of nine months (August 2005-April 2006). The survey was conducted on 90 fish farmers of 52 villages under 6 unions. Data were collected through personal visit and interviews following a detailed questionnaire. Pond sizes of the area varied from 15 to above 180 decimal of which maximum ponds (57.8%) were operated by single owner. Field observation revealed that 65.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 1 publication
2
13
1
Order By: Relevance
“…In addition, lack of scientific knowledge and suitable technology, lack of extension services on aquaculture training, occurrences of fish diseases, water scarcity during drought season, pond water irrigation for crop fields were found harmful for aquaculture production in the study area. Similar observation was also made by Zaman et al (2006) in Mohanpur, Rajshahi.…”
Section: Problems Of Fish Farmingsupporting
confidence: 88%
See 1 more Smart Citation
“…In addition, lack of scientific knowledge and suitable technology, lack of extension services on aquaculture training, occurrences of fish diseases, water scarcity during drought season, pond water irrigation for crop fields were found harmful for aquaculture production in the study area. Similar observation was also made by Zaman et al (2006) in Mohanpur, Rajshahi.…”
Section: Problems Of Fish Farmingsupporting
confidence: 88%
“…However, education level was comparatively better than the fish farmers of haor fishermen reported by Mahbubur (2001) where he found the illiteracy rate as 68%. Zaman et al (2006) also reported 23.3% farmers were illiterate in Mohanpur, Rajshahi.…”
Section: Educational Statusmentioning
confidence: 87%
“…They, therefore, have to involve as it is readily available livelihood in order to support their family. A study by Zaman et al (2006) involving 90 fish farmers of 52 villages under 6 unions in Mohanpur upazila indicated similar result where 87.8 percent were married and 12.2 percent were unmarried.…”
Section: Socioe-conomic Profile Of the Respondent Fishermenmentioning
confidence: 69%
“…Mahmud et al (2015) found that 46%, 14% and 2% peoples had passed primary, secondary and higher secondary, respectively at Paira river, Patuakhali. Zaman et al (2006) reported that 23.3% fishers were illiterate whereas 14.4%, 8.9% and 6.7% were educated up to primary, secondary and higher secondary or above level, respectively at Mohanpur Upazila in Rajshahi District.…”
Section: Educational Levelmentioning
confidence: 99%